Obstructive sleep apnea, intermittent hypoxemia and prothrombotic biomarkers - Deokar, Kunal; Meshram, Sushant; Chawla, Gopal; Kunjir, Nana; Meshram, Chetna; Abrol, Nupur; Gaikwad, Priyanka (Sleep Science, 2020)
Objective To study the serum levels of fibrinogen and d-dimer in patients with obstructive sleep apnea (OSA) and its correlation with apnea hypopnea index (AHI), oxygen desaturation index (ODI), minimal oxygen saturation and arousal index.Methods It was a case control study in which 23 cases of OSA and 23 controls were enrolled. Morning fasting serum fibrinogen and d-dimer were measured in cases of OSA and controls.Results Serum fibrinogen levels among OSA patients (268.47±53.11mg/dl) were elevated as compared to the levels in controls (221.52±65.84mg/dl) (p<0.05). Serum fibrinogen co-related positively with AHI (r=0.6381, p=0.0011) and ODI (r=0.7434, p=0.0000), negatively with minimal oxygen saturation (r=-0.4461, p=0.0329). There was no statistically significant correlation of fibrinogen with arousal index (r=0.2697, p=0.2133). There was no statistically significant difference between mean fasting d-dimer level in cases (0.12mg/L, 0.06±0.18mg/L) and controls (0.12mg/L, 0.02±0.22mg/L) (p=0.8926).Conclusions The observation of elevated fibrinogen levels with the increasing severity of OSA and hypoxemic events makes OSA one of the important risk factor for cardiovascular disorders.
Keywords: Sleep Apnea Syndrome; Fibrinogen; Hypoxia